Systematic Literature Review: Evaluation of Financial Performance Before and After Mergers and Acquisitions in the Banking Sector - Endah Kusumastuti; Nicko Albart; Nurul Huda (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Mergers and Acquisitions (M&A) are an effective strategy that can be carried out by companies including banks to increase capital, expand business and create financial stability. This research evaluates the financial performance of banks that did mergers and acquisitions. This research uses a Systematic Literature Review to obtain results by collecting various research journals related to M&A using a published search system that focuses on Google Scholar, Crossref, Semantic and Science Direct as sources of journals. The results of this research show that the impact of M&A on financial performance in the banking sector is variative. The result of this study is M&A has significant impact to financial performance commercial banks but not significant for public banks. M&A can have a significant impact if done voluntarily. On the other hand, M&A can also have an insignificant impact if the M&A is carried out with aim only for saving the company target and not focused on increasing the company's value.